IN VITRO EFFICACY OF EXTRACTS FROM PLANTS USED BY SMALL-HOLDER FARMERS IN THE TREATMENT OF DERMATOPHILOSIS IN CATTLE - Ndhlovu, Daud N; Masika, Patrick J (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Bovine dermatophilosis, an important skin disease of cattle caused by Dermatophilus congolensis, negatively impacts the livelihoods of small-holder farmers in Zimbabwe. This impact is through, morbidity, loss of draught animal power, costs incurred to manage the disease, losses associated with devalued damaged hides and the resultant culling of some of the affected cattle. Due to the inaccessibility of conventional drugs to manage bovine dermatophilosis, farmers have been reported to use local medicinal plants to manage the disease. The aim of the study was to evaluate the in vitro antimicrobial activities of three plants that small-holder farmers in Zimbabwe used to manage bovine dermatophilosis. Methods: Dried plant materials were ground into powder and extracted individually using, water, 80 % acetone and 80 % methanol. The antimicrobial properties of the plants were evaluated against two Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and one Gram-positive (Staphylococcus aureus) reference bacterial strains. They were further evaluated against a field isolate of Dermatophilus congolensis. The assays used were the disc diffusion, minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). Results: Acetone and methanol extracts had superior inhibitory activities than did those of water. Pterocarpus angolensis DC extracts had better inhibitory properties with absolute MIC values of 0.156 – 5 mg/ml, Cissus Quadrangularis L had MIC values in the range 0.156 – 5 mg/ml while that of Catunaregam spinosa Thunb, Terveng was 0.156 – 10 mg/ml. Dermatophilus congolensis was more sensitive to Pterocarpus angolensis DC average MIC = 0.63 mg/ml than to Cissus quadrangularis L average MIC = 1.25 mg/ml and Catunaregam. spinosa Thunb, Terveng average MIC = 2.08 mg/ml. Conclusion: These results suggest the potential antibacterial activities of extracts of the three plants and hence farmers are, in a way, justified in using the plants. Better results (lower MIC) could be obtained by extracting and evaluating pure active compounds of the plants.